A A CONTENT ANALYSIS OF TEACHER’S MORPHOLOGICAL AWARENESS IN TEACHING PAST TENSE VERBS THROUGH YOUTUBE - Pitriyah; Dewanti, Ratna (J-LEE - Journal of Law, English, and Economics, 2024)
This study examines the teacher's morphological awareness in teaching English, specifically focusing on the past-tense verb forms. The analysis is based on a YouTube instructional video titled "Pembelajaran Bahasa Inggris Kelas 8 SMP: Simple Past Tense," the objective is to identify the application of morphological theories in teaching method employed. The research questions based on three primary aspects: The morphological awareness indicators evident in the teaching techniques used by the teacher in the video; The extent to which the teacher uses morphemes to teach past tense; The ways used by the teacher to demonstrate the application of theories and strategies of teaching past tense verbs in the instructional video. The results indicate that the teacher demonstrates a strong understanding of morphological awareness, clearly explaining verb changes, and applying interactive educational techniques. The study highlights the significance of morphological awareness in language instruction and proposes that digital platforms such as YouTube might improve the teaching and learning process. The research provides useful insights into the implementation of morphological awareness in classroom settings and offers recommendations for additional research and practice. Despite its emphasis on a single YouTube video, this study not only improves comprehension of morphological awareness in digital contexts, but it also offers practical solutions for educators to improve grammar teaching effectiveness. Keywords: content analysis, digital platforms language teaching techniques, morphological awareness, past tense verbs.